Responses of tropical plankton communities from the Mexican Caribbean to solar ultraviolet radiation exposure and increased temperature - Halac, Silvana Raquel (2013)
The aim of this study was to evaluate the effects of UVR on growth and taxonomic composition of tropical plankton communities in a scenario of increased temperature and ultraviolet radiation. Water samples were collected from a reef lagoon in the Mexican Caribbean (20.5° N, 86.5° W) during July 2010 and grown for 16 days in microcosms under two natural radiation treatments: a) PAB (PAR + UV-A + UV-B, 280–700 nm) and, b) P, (PAR, 400–700 nm) and two temperature conditions: a) ambient (28 °C), and, b) increased (ambient + 3 °C). A differential factorial response of the studied variables among the main taxonomic groups and more frequent species was found. The biomass of dinoflagellates and colorless plankton was negatively affected by UVR while the increased temperature had negative effects on diatom biomass and cell abundance. During the experimental period there were changes in the contribution of each taxonomic group. At ambient temperature there was a shift from a flagellate- to a diatom-dominated community; whereas at increased temperature diatoms co-dominated with flagellates. UVR exposure decreased the contribution of naked dinoflagellates (> 20 μm) and cryptophytes. On the other hand, the most frequent diatom, Cylindrotheca closterium was negatively affected at increased temperature, while small chlorophytes (< 10 μm), which were one of the dominant groups of flagellates, contributed significantly to the biomass at increased temperature at the end of the experiment. Synergistic effects of UVR and temperature were only detected at the species level in large diatoms (> 20 μm; e.g. Leptocylindrus sp. and Amphora sp.) and in cryptophytes (> 10 μm). Our results suggest that planktonic assemblages from the Mexican Caribbean are generally well-adapted to the high UVR fluxes and temperature with some species being positively influenced by increased temperature. However there are exceptions with some species being negatively affected by UVR, increased temperature or the combination of both factors. Therefore, our results indicate that under the high radiation conditions of tropical oceans, changes in community structure in terms of taxonomic composition and size distribution would occur in a scenario of global climate change.